Targeted next-generation sequencing of locally advanced squamous cell carcinomas of the head and neck reveals druggable targets for improving adjuvant chemoradiation - Tinhofer, Ingeborg; Budach, Volker; Saki, M.; Konschak, R.; Niehr, F.; Joehrens, K.; Weichert, W.; Linge, Annett; Lohaus, Fabian; Krause, Mechthild; Neumann, K.; Endris, V.; et al. (European Journal of Cancer, 2016)
Background Despite clear differences in clinical presentation and outcome, squamous cell carcinomas of the head and neck (SCCHN) arising from human papilloma virus (HPV) infection or heavy tobacco/alcohol consumption are treated equally. Next-generation sequencing is expected to reveal novel targets for more individualised treatment. Patients and methods Tumour specimens from 208 patients with locally advanced squamous cell carcinoma of the hypopharynx, oropharynx or oral cavity, all uniformly treated with adjuvant cisplatin-based chemoradiation, were included. A customised panel covering 211 exons from 45 genes frequently altered in SCCHN was used for detection of non-synonymous point and frameshift mutations. Mutations were correlated with HPV status and treatment outcome. Results Mutational profiles and HPV status were successfully established for 179 cases. HPV- tumours showed an increased frequency of alterations in tumour suppressor genes compared to HPV+ cases (TP53 67% versus 4%, CDKN2A 18% versus 0%). Conversely, HPV+ carcinomas were enriched for activating mutations in driver genes compared to HPV- cases (PIK3CA 30% versus 12%, KRAS 6% versus 1%, and NRAS 4% versus 0%). Hotspot TP53 missense mutations in HPV- carcinomas correlated with an increased risk of locoregional recurrence (hazard ratio [HR] 4.3, 95% confidence interval [CI] 1.5-12.1, P = 0.006) and death (HR 2.2, 95% CI 1.1-4.4, P = 0.021). In HPV+ SCCHN, driver gene mutations were associated per trend with a higher risk of death (HR 3.9, 95% CI 0.7-21.1, P = 0.11). Conclusions Distinct mutation profiles in HPV- and HPV+ SCCHN identify subgroups with poor outcome after adjuvant chemoradiation. Mutant p53 and the phosphoinositide 3-kinase pathway were identified as potential druggable targets for subgroup-specific treatment optimisation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Adjuvant chemoradiation; Cisplatin; Head and neck cancer; Human papilloma virus; Mutation profiles